2017 3DTV Conference: The True Vision - Capture, Transmission and Display of 3D Video (3dtv-Con) 2017
DOI: 10.1109/3dtv.2017.8280417
|View full text |Cite
|
Sign up to set email alerts
|

Extreme field-of-view for head-mounted displays

Abstract: We present novel optics and head-mounted display (HMD) prototypes, which have the widest reported field-of-view (FOV), and which can cover the full human FOV or even beyond. They are based on lenses and screens which are curved around the eyes. While this is still work-in-progress, the HMD prototypes and user tests suggest a feasible approach to significantly expand the FOV of HMDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Our proof-of-concept prototype (Sand et al, 2015) enables users to touch and feel virtual 3D objects without the need for wearable devices. A superwide field-of-view (FOV) optical design for VR glasses (Rakkolainen et al, 2016;Rakkolainen et al, 2017b) can cover even the full human FOV. Recently we have also experimented with extending the FOV of a VR viewing device (Rakkolainen et al, 2017a) and providing visual feedback for a smart glass user directly to the retinasurpassing the eye and its lens (Koskinen et al, 2017).…”
Section: Augmented Sensesmentioning
confidence: 99%
“…Our proof-of-concept prototype (Sand et al, 2015) enables users to touch and feel virtual 3D objects without the need for wearable devices. A superwide field-of-view (FOV) optical design for VR glasses (Rakkolainen et al, 2016;Rakkolainen et al, 2017b) can cover even the full human FOV. Recently we have also experimented with extending the FOV of a VR viewing device (Rakkolainen et al, 2017a) and providing visual feedback for a smart glass user directly to the retinasurpassing the eye and its lens (Koskinen et al, 2017).…”
Section: Augmented Sensesmentioning
confidence: 99%
“…It was observed during some of the SbS tests in the VR, although not measured directly, that the test subject either tried to fall back slightly behind the pacer, so that the pacer was within their sight, or turned their head towards the pacer. This intermittent behaviour might have been the result of the limited horizontal field of view (FoV) provided by the HMD, confined to around 90 degrees [ 100 ]. In comparison, the unobstructed FoV of an average human spans approximately 200 degrees in the horizontal direction [ 101 ], which is significantly more than that of the HMD.…”
Section: Discussionmentioning
confidence: 99%
“…This intermittent behaviour might have been the result of the limited horizontal field of view (FoV) provided by the HMD, confined to around 90 degrees [100]. In comparison, the unobstructed FoV of an average human spans approximately 200 degrees in the horizontal direction [101], which is significantly more than that of the HMD. It was previously shown that limiting horizontal FoV can impact one's perception of space [102], which might have led to more conscious stepping behaviour.…”
Section: Qualitative Differences Between Is Tests In Rl and Vrmentioning
confidence: 99%
“…Design elements for visual senses consist of a field of view (FOV), field of regard (FOR), visual illusions, color, depth, scale, and framing. Current HMD's provide have 100-degree horizontal and 110-degree vertical FOV (Rakkolainen et al, 2017), and 360-degrees horizontal and vertical FOR (Jerald, 2016). Thus, the current VR technology allows the player to look in all directions in the virtual environment by turning his head.…”
Section: Perceptionmentioning
confidence: 99%